Retrieved (Technical Condition Analysis of Main Structures of Yerevan Lake Hydro Facility) - Sarukhanyan, Arestak; Kelejyan, Hovhannes; Sahakyan, Aram (Scientific Papers of National University of Architecture and Construction of Armenia, 2024)
Retrieved. The article already published under the serial number 2023/2(89) was republished as a result of a technical issue.